The Importance of Critical Thinking Skills in Elementary School Students in Social Studies Subjects - Nabila Hafifah; Nisa, Sahrun; Suriani, Ari (PT FORMOSA CENDEKIA GLOBAL, 2024)
Critical thinking skills are an important aspect in teaching social studies to elementary school students. In the era of globalization and Industry 4.0, these skills are key in managing complex change. This article discusses the importance of developing critical thinking skills in elementary school students in the context of social studies learning. Critical thinking involves interpreting, analyzing, and evaluating information and experiences. This research uses literature research methods to analyze several journals that discuss critical thinking skills, student characteristics, and social studies learning in elementary schools. The results show that critical thinking is effective in improving students' thinking abilities. Indicators of critical thinking skills include reporting observation results, formulating questions, generalizing data, answering the question